THE IMPLEMENTATION OF “DICTOGLOSS” IN TEACHING LISTENING TO A NARRATIVE TEXT TO THE EIGHTH GRADERS (RETAIN, 2016)
THE IMPLEMENTATION OF “DICTOGLOSS” IN TEACHING LISTENING TO A NARRATIVE TEXT TO THE EIGHTH GRADERS Lussy Hendryanti English Department, Languages and Arts Faculty, The State University of Surabaya Email: lussyhendryanti@mhs.unesa.ac.id Dra. Theresia Kumalarini, M. Pd. English Department, Languages and Arts Faculty, The State University of Surabaya Email: theresiakumalarini@unesa.ac.id Abstract This study aims to describe the implementation of Dictogloss in the teaching of listening to a narrative text and the students’ response toward the listening activity while using it. There are eight types of Dictogloss technique one of which used in this study is a Summary Dictogloss. This study is a qualitative research, the data of which were collected through observation checklist and questionnaire. The observation was done in three meetings and at the last meeting the questionnaire was given. The observation checklist was analyzed by coding the indicators and the questionnaire by using descriptive statistics. The observation result shows that the teacher has followed the theory of teaching listening and Dictogloss steps. In addition, the questionnaire result shows that the students response positively toward the implementation of Dictoglos in a listening class. Keywords: Listening, Narrative Text, Dictogloss, Response Abstrak Penelitian ini bertujuan untuk mendeskripsikan implementasi Dictogloss pada kegiatan mengajar ketampilan mendengarkan teks naratif dan respon siswa pada proses pembelajaran tersebut.. Ada delapan variasi di dalam teknik Dictogloss, diantara delapan variasi itu, peneliti mengobservasi pelaksaan Dictogloss Summary. Penelitian ini merupakan penelitian kualitatif yang datanya diambil melalui lembar observasi dan kuisioner. Observasi dilakukan dalam 3 pertemuan dan membagikan kuisioner pada pertemuan terakhir. Peneliti menganalisa lembar observasi dengan mengelompokkan sesuai indikator observasi dan kuisioner dianalisa dengan menggunakan uji deskripsi statistik. Hasil observasi menunjukkan bahwa guru mengajar sesuai dengan teori ketrampilan mendengarkan dan langkah – langkah Dictogloss. Selain itu, hasil kuisioner menunjukkan bahwa siswa memberikan respon positif dalam implementasi Dictogloss pada kegiatan mengajar ketampilan mendengarkar. Kata Kunci: Mendengarkan, Teks Naratif, Dictogloss, Respon